2011
DOI: 10.1038/hr.2011.100
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in ambulatory blood pressure monitoring in hypertensive patients with diabetes

Abstract: on behalf of the Spanish Society of Hypertension ABPM Registry investigators 9Our aim was to assess the ambulatory blood pressure monitoring (ABPM) characteristics or patterns in hypertensive patients with diabetes compared with non-diabetic hypertensives. We performed a cross-sectional analysis of a 68 045 patient database from the Spanish Society of Hypertension ABPM Registry, a nation-wide network of 41200 primary-care physicians performing ABPM under standardized conditions in daily practice. We identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 30 publications
1
31
0
7
Order By: Relevance
“…Corresponding data in renal and coronary heart disease patients were 72.1 and 25.8%, and 69.4 and 25.1%, respectively. 23 A relationship between the level of BP and the non-dipper pattern has also been reported, according to data from our group 21 (Table 1). Patients showing most elevated ambulatory systolic BP (4155 mm Hg) showed a prevalence of non-dippers of E70%.…”
Section: Circadian Bp Variation and Risk Categoriesmentioning
confidence: 82%
“…Corresponding data in renal and coronary heart disease patients were 72.1 and 25.8%, and 69.4 and 25.1%, respectively. 23 A relationship between the level of BP and the non-dipper pattern has also been reported, according to data from our group 21 (Table 1). Patients showing most elevated ambulatory systolic BP (4155 mm Hg) showed a prevalence of non-dippers of E70%.…”
Section: Circadian Bp Variation and Risk Categoriesmentioning
confidence: 82%
“…These differences have been related, at least in part, with a wider use of antihypertensive drug combinations in the United States. Many treated patients in the Spanish ABPM Registry were receiving combinations of antihypertensive drugs, particularly high-risk hypertensives [24,25,33]. Despite a predominant use of combinations, the majority of patients had undercontrolled ambulatory BP.…”
Section: The Burden Of Uncontrolled Hypertensionmentioning
confidence: 99%
“…A series of analyses from the Spanish ABPM Registry have assessed prevalence of white-coat and masked hypertension in general treated hypertensives [17,19], untreated hypertensives [18], treated male vs. female hypertensives [20], hypertensives with coronary heart disease [21], very elderly hypertensives [22], resistant hypertensives [23], diabetics [24] and hypertensives with chronic kidney disease [25]. Prevalence of white-coat hypertension ranged from 15Á5% to 29Á2% in untreated patients, and prevalence of white-coat false resistance ranged from 24Á2% in treated males to 37Á5% in hypertensives resistant to three or more drugs.…”
Section: Prevalence Of White-coat and Masked Hypertensionmentioning
confidence: 99%
“…In this issue of Hypertension Research, Gorostidi et al, 11 drawing on data from a Spanish database, describe patterns of ABPM in hypertensive patients with or without diabetes. The authors found that diabetic patients have higher BP levels and are more likely to be non-dippers; the riser pattern in particular was more frequent than in nondiabetic patients.…”
mentioning
confidence: 99%